Frequency and Inertial Response Analysis of Loads in the Chilean Power System - Chavez-Orostica, H; Diaz-Diaz, M; Fuentes-Parra, C; Quiroz-Moreno, J (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The integration of power electronics-interconnected generation systems to the grid has fostered a significant number of concerns on power system operations, particularly on the displacement of synchronous generators that leads to a reduction in the grid’s overall inertia and frequency response. These concerns have raised a significant amount of state-of-the-art mathematical proposals on how to estimate system inertia; however, the majority of the proposals do not differentiate generator inertia from load inertia. When inertia prediction for control room applications is required in real-time, the current state-of-the-art proposals use the inertia of generators as a proxy for a minimum, overall inertia estimate, counting the number of units committed in real-time and adding up their inertia. However, as dynamic conditions are becoming challenging with the integration of power electronics-interconnected generation systems, it is important to quantify the amount of inertia from the loads, for which the state-of-the-art proposals present very limited advancement, particularly in applications with real data. This work presents a set of recorded actual events in the Chilean power system to estimate the contribution of loads to inertia and frequency response to assess whether the loads have a significant role in frequency stability. The contribution of this work is as follows: first, reporting real data of a power system from the PMU and SCADA systems that are usually classified as not public; and, second, to derive a conclusion from the data to assess the role of loads in frequency stability in a real case. © 2023 by the authors.